Cost-benefit Analysis of Earthquake Costs and Building Retrofitting Costs in Iran - Fariborz Mohammadi; Shahabodin Fuladi Moghaddam; Iman Shabanzadeh; Shahin Behdarvand (Health in Emergencies & Disasters Quarterly)
Background: This article examines the cost of financial damages caused by earthquakes in the building sector and compares it with the estimation of retrofitting in Iran. This study compares the costs of two scenarios: “Action after the earthquake” and “strengthening the structures before the earthquake.” Materials and Methods: In this study, data obtained from governorates and building retrofitting engineering companies have been used. The scope of the study is earthquakes that occurred in the geographical area of ​​Iran. Among them, 8 earthquakes were specifically studied: Mianeh, Ahar and Haris, Qator, Murmori, Khorasan, Damghan and Shahroud, Goharan, Hormozgan and Ezgele. Using the time value of money method to the value of 2021, we converted the estimated and realized costs to enable comparison and aggregation. Results: The cost-benefit comparison of policies of action after the earthquake and retrofitting before the earthquake shows that Iran has suffered as much as 238 million USD in losses due to the lack of building resilience against earthquakes. The results show that the policy of retrofitting structures before an earthquake is significantly more optimal than the other scenario. Conclusion: The comparison of the two policy scenarios examined in this study shows that retrofitting buildings before an earthquake, on the one hand, prevents vast losses, and on the other hand, increasing the number of earthquake-resistant houses reduces the amount of earthquake damage.